2005
DOI: 10.1093/tropej/fmi067
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation and Cluster Analysis of Parapneumonic Effusion in Childhood

Abstract: We studied 80 children with parapneumonic effusion (PPE) with respect to the clinical manifestations and treatment alternatives as well as prospective follow-up for 1 year. Out of the 80 patients, 59 per cent were male. The mean age of the patients was 4.0 +/- 3.1 years. Mild effusion was successfully treated by antibiotic alone in 33 per cent of the patients. Tube thoracostomy (TT) was utilized in 63 per cent of the patients. In this group, 11 healed completely, 13 patients required surgical treatment, and 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
2
0
1
Order By: Relevance
“…Two different studies reported the rate of empyema in cases with pleural effusion to be 60.3% and 61.7% (8,19). Staphylococcus aureus, S. pneumoniae and S. pyogenes have been reported as the most common pathogens causing empyema in children (7)(8)(9)(10)(19)(20). In our study, the pathogens were similar to those reported in the literature, although the rate of Streptococcus pyogenes was higher.…”
Section: Discussionsupporting
confidence: 85%
“…Two different studies reported the rate of empyema in cases with pleural effusion to be 60.3% and 61.7% (8,19). Staphylococcus aureus, S. pneumoniae and S. pyogenes have been reported as the most common pathogens causing empyema in children (7)(8)(9)(10)(19)(20). In our study, the pathogens were similar to those reported in the literature, although the rate of Streptococcus pyogenes was higher.…”
Section: Discussionsupporting
confidence: 85%
“…Other reports revealed mild restrictive or obstructive abnormalities in children tested at least 1 year from the initial infection. Abnormal lung function in four out of eight children was found by Hacimustafaoglou et al, tested 1 year after PPE. Obstructive pattern in spirometric parameters has been noted by Hartl et al, in 8 out of 14 children with empyema.…”
Section: Discussionmentioning
confidence: 72%
“…Lung abscess and empyema thoracis: The single available study 84 suggested that lung abscess develops more often in men than in women. The studies that examined patients with empyema thoracis [85][86][87] came up to the same conclusions.…”
Section: Sex Differences In the Incidence And Severity Of Rtismentioning
confidence: 67%